CFD simulation on oil-water annular flow through CAF generator device. Issue 15 (2nd August 2020) - Jiang, Wenming; Wu, Junqiang; Du, Shilin; Liu, Chengsong; Liu, Yang
ABSTRACT: The technology of heavy oil transportation by core-annular flow (CAF) is attracting more and more attention. In this paper, the flow of oil-water annular flow in a 19 mm horizontal pipe in the presence of a CAF generator is studied by using the Volume of Fluent (VOF) model in Fluent 14.5. A detailed study of oil-water flow in the CAF generator device and effects of variation of gap thickness is analyzed, and the pressure distribution of CAF after passing through the CAF generator is discussed. The phase distribution obtained by numerical calculation agrees well with the experimental results. The influence of spiral blade on oil-water annular flow in CAF generator device is also analyzed. The results provide a suitable reference for the formation of CAF.